The Minimalist Approach to Online Instructional Videos - Pflugfelder, Ehren Helmut (Technical Communication, 2013)
Purpose: The instructional project described in this article explores a model for reconceptualizing a form of short video instruction manual termed here as the "Web app video." The goal is to determine whether explicit instruction in minimalism can help students (and practitioners) apply such principles and heuristics to the genre of Web app videos and aid in invention within emergent documentation scenarios. Method: An instructional method was used in this study, specifically the introduction of minimalist documentation concepts and heuristics to instructional video production. This study compares assessment rubrics completed by students as pre-and post-test assessment data, though the success of the instructional method is not dependent upon these results. Results: After working with minimalism heuristics, student-produced videos showed greater attention to imperative mood language, task-orientation, and error representation than existing videos for Web applications. Though student-produced videos lacked production polish, they showed evidence of minimalist strategies. Conclusions: Minimalist documentation strategies can be successfully taught and applied to short videos designed to entertain, encourage, inform, and instruct potential users while enabling them to engage the Web application with more knowledge.
https://katalog.adlr.link/Record/ai-55-aHR0cDovL3d3dy5qc3Rvci5vcmcvc3RhYmxlLzQzMDkzMDY1